Exploring the effects of Korean subject marking and action verbs' repetition frequency: How they influence the discourse and the memory representations of entities and events - Kim, Lucy Kyoungsook (ProQuest Dissertations & Theses, 2015)
Language and memory are two of the most fundamental components of human cognition. Individuals’ linguistic performance relies greatly on memory competence. At the same time, linguistic expressions can also influence what comprehenders remember and how well they remember it. Due to the close connection between these two cognitive domains, it is important to study how linguistic descriptions can influence the representations that language users build in their minds and how those representations are reflected in discourse and memory. This dissertation investigated the interplay between language and memory in the areas of entity representation denoted by nouns and event information denoted by verbs. Combining research on nominal information and verbal information is beneficial for our understanding of language processing as they are two vital aspects of sentence meaning. In the nominal domain, I conducted three experiments to explore the effect of Korean subject case marking, more specially the difference between the nominative case marker and the topic case marker (when interpreted as marking a contrastive topic). My results show that how subjects are interpreted (e.g., a default topic or a contrastive topic) has an effect on comprehenders’ expectations about which entities will be mentioned in upcoming discourse. Furthermore, the experiments also show that the order in which characters are introduced in a story influences how well comprehenders recognize them in a memory task (i.e., a recently-mentioned entity is recognized more accurately than an earlier-mentioned entity). However, a follow-up off-line story continuation task revealed that the entity that comprehenders remembered better is not the entity they talk about frequently in story continuation. Rather, the first-mentioned character was mentioned more often in subsequent sentences. Put together, my results point to a possible disconnect between accessibility in discourse and accessibility in memory: An entity’s prominence in discourse and memory are not always parallel. This suggests that prominence is a multifaceted concept that can be a product of many different factors including: (i) how and where in the discourse an entity is introduced; (ii) who else is in the discourse; and (iii) different reading goals that can affect language processing strategies. In the verbal domain, I investigated whether and how the frequency semantics of an action verb would influence sentence processing. My results show that comprehenders’ sensicality judgment was more accurate for the sentences containing action verbs of low intrinsic repetition frequency (i.e., actions which typically only happen once or twice in a row) compared to the sentences denoting high frequency actions (i.e., actions which typically happen multiple times in a row). Moreover, in a verb recognition task, verbs of low repetition frequency were recognized more accurately than verbs of high repetition frequency. These results add to the existing literature that demonstrates the effect of other semantic properties that have been shown to influence comprehenders’ linguistic and nonlinguistic behaviors. Those semantic aspects include the speed of an action, the duration of a motion, and physical effort necessary for a motion. Combining all these results, this dissertation emphasizes the importance of investigating individuals’ language processing strategies from diverse perspectives including: (i) comparing how an entity is represented in discourse and in memory; (ii) investigating both nominal information and verbal information in a sentence; and (iii) investigating multiple factors that influence a linguistic concept’s accessibility in discourse and in memory.